In vitro oxidized HDL and HDL from type 2 diabetes patients have reduced ability to efflux oxysterols from THP-1 macrophages - Chen, Yinan; Arnal-Levron, Maud; Hullin-Matsuda, Françoise; Knibbe, Carole; Moulin, Philippe; Luquain-Costaz, Céline; Delton, Isabelle (Biochimie, 2018)
Oxidized LDL (OxLDL) that are enriched in products of lipid peroxidation including oxysterols have been shown to induce cellular oxidative stress and cytotoxicity therefore accelerating atheroma plaque formation. Upon oxLDL exposure of THP-1 macrophages, intracellular oxidation of LDL derived-cholesterol as well as endogenous cholesterol was increased. The oxysterols intracellularly produced were efficiently exported to HDL whereas apolipoprotein A1 was inefficient. These findings prompted us to investigate the consequences of modification of HDL by oxidation and glycation as observed in type 2 diabetes with respect to oxysterol and cholesterol efflux. We show that efflux of oxysterols was significantly impaired after in vitro oxidation and glycoxidation of HDL whereas glycation alone had no impact. Cholesterol efflux was only slightly decreased by oxHDL or glycoxidized HDL and not changed with glycated HDL. The defect of HDL towards oxysterol efflux was also observed with HDL isolated from diabetic subjects as compared to healthy controls. These findings support a deleterious cellular retention of oxysterols due to dysfunctional HDL in type 2 diabetes. [Display omitted] •In vitro oxidized and glycoxized HDL have reduced ability to efflux oxysterols from THP-1 macrophages.•In vitro glycated HDL are as efficient as control HDL.•HDL from diabetic patients are less efficient to promote oxysterol efflux as compared to HDL from healthy subjects.•HDL from healthy subjects contain low amounts of oxysterols that are even less in HDL from diabetic patients.